2012
DOI: 10.1017/s1751731111001248
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of milk oligosaccharides and lactose: a hypothesis

Abstract: Mammalian milk or colostrum contains up to 10% of carbohydrate, of which free lactose usually constitutes more than 80%. Lactose is synthesized within lactating mammary glands from uridine diphosphate galactose (UDP-Gal) and glucose by a transgalactosylation catalysed by a complex of b4-galactosyltransferase and a-lactalbumin (a-LA). a-LA is believed to have evolved from C-type lysozyme. Mammalian milk or colostrum usually contains a variety of oligosaccharides in addition to free lactose. Each oligosaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 30 publications
2
57
0
3
Order By: Relevance
“…Tammar wallaby milk does not contain oligosaccharides whose core units are lacto-N-neotetraose (Gal(β1-4)GlcNAc(β1-3)Gal (β1-4)Glc) or lacto-N-neohexaose (Gal(β1-4)GlcNAc(β1-3)[Gal(β1-4)GlcNAc(β1-6)]Gal(β1-4)Glc), unlike the milk of several eutherian species [2,3,16,17]. In addition, galactosyllactoses such as those found in tammar wallaby milk other than Gal(β1-3)Gal(β1-4)Glc, have never been found in any eutherian milk/colostrum [2,3,16,17]. However, lacto-N-novopentaose I has been found in the milk/ colostrum of both the tammar wallaby and a few eutherian species including cow [18][19][20], camel [11], pig [21], horse [22] and capuchin monkey [23].…”
Section: Discussionmentioning
confidence: 99%
“…Tammar wallaby milk does not contain oligosaccharides whose core units are lacto-N-neotetraose (Gal(β1-4)GlcNAc(β1-3)Gal (β1-4)Glc) or lacto-N-neohexaose (Gal(β1-4)GlcNAc(β1-3)[Gal(β1-4)GlcNAc(β1-6)]Gal(β1-4)Glc), unlike the milk of several eutherian species [2,3,16,17]. In addition, galactosyllactoses such as those found in tammar wallaby milk other than Gal(β1-3)Gal(β1-4)Glc, have never been found in any eutherian milk/colostrum [2,3,16,17]. However, lacto-N-novopentaose I has been found in the milk/ colostrum of both the tammar wallaby and a few eutherian species including cow [18][19][20], camel [11], pig [21], horse [22] and capuchin monkey [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although L. casei can be cultured on LNB as the only carbon source, the simultaneous presence of GNB and LNB in environments such as the gastrointestinal tract of breast-fed infants would possibly enhance the efficiency of LNB utilization. GNB and LNB form part of a great variety of bioactive molecules, such as HMO, glycosphingolipids, mucin glycoproteins and glycolipids (Hakomori, 2008;Thurl et al, 2010;Moran et al, 2011;Urashima et al, 2012;Liu and Newburg, 2013). In order to be used by L. casei, they must be previously released from those glycocomplexes by the action of other microbial glycosidases.…”
Section: Et Al 2009mentioning
confidence: 99%
“…GNB is also a crucial structure in functional sugar chains like the T-antigen disaccharide and it is also an essential part of the carbohydrate moieties of complex glycosphingolipids (Lloyd et al, 1996;Moran et al, 2011;Liu and Newburg, 2013). Another important disaccharide present in human secretions is lacto-N-biose (LNB; Galβ1-3GlcNAc), which is the major core structure of human milk oligosaccharides (HMO) (Thurl et al, 2010;Urashima et al, 2012). HMO are classified into type-1 and type-2, containing LNB and N-acetyllactosamine, respectively, as disaccharide building blocks.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that monotreme lactation originally evolved to prevent desiccation of the eggs or for protection against microbes, and subsequently evolved a nutritional role (Warren et al 2008; Oftedal 2012, 2002b; Urashima et al 2012). Several studies have shown that a variety of antimicrobial proteins are expressed in either mammary glands or milk in marsupials, humans, cow and mouse, and these factors are believed to contribute to a lower incidence of infections (Aniansson et al 1990; Strömqvist et al 1995; Murakami et al 2005; Hettinga et al 2011; Nicholas et al 2012; Dallas et al 2013).…”
Section: Introductionmentioning
confidence: 99%